Protection Of Domestic Workers In A Comparison Of The Laws Of Indonesia And The Philippines - Pranitiaz, Laras Medina; Citraresmi Widoretno Putri (Dinasti Research, 2025)
Domestic Workers (DWs) are a group that is vulnerable to rights violations and exploitation. ILO Convention No. 189 regulates protection standards for DWs, but its implementation is limited because not all countries have adopted these provisions. In Indonesia, the absence of clear regulations has led to a legal vacuum and weak protection of the rights of DWs. In contrast, the Philippines has specific regulations through the Kasambahay Law, which provides more comprehensive protection. The purpose of this study is to review the forms of legal protection for DWs in Indonesia and the Philippines and to examine the impact of the legal vacuum in Indonesia. The method used is normative juridical with a conceptual and comparative approach. The results of this study show that Indonesia still lags far behind the Philippines in providing protection for DWs. This condition reflects the need for concrete efforts by the Indonesian government to reform the existing system by adopting the best practices implemented in the Philippines to strengthen the national legal framework, reduce violations, and improve the welfare of DWs.